Experiment and method of maize ear threshing under airflow mixed impact - Li, Yanan; Li, Xinping; Hou, Jiarui; Wang, Junyi; Peng, Bin; Sun, Ruizhe (International Journal of Agricultural and Biological Engineering, 2026)
This study addresses the high breakage rates in the traditional mechanical processing of maize kernels. This paper examines force transfer and consumption within longitudinal and transverse force chain networks by integrating high-speed low-flow and low-speed high-flow methodologies. A mathematical model was developed, incorporating the concept of contact force. Using factors such as airflow impact angle, direction, and regions of maize ears as test variables, three-dimensional force values and threshing quantities were analyzed as key performance indicators. The investigation explored the relationship between three-dimensional forces, destructive forces, and these test factors while examining changes in primary impact forces. High-speed photography was employed to validate the established threshing rules and trajectories. Results indicated that contact forces among different regions of a maize ear were approximately equal. Under specified conditions, transverse threshing was more efficient than longitudinal threshing. The magnitude of the three-dimensional forces followed the order of Z-direction > Y-direction > X-direction, indicating that the predominant impact occurs primarily along the Z-axis. For the force values in each direction and region, the large sections exhibited the highest forces, followed by the middle sections, while the small sections displayed the lowest overall forces. Additionally, longitudinal three-dimensional force values exceeded those measured transversely. The destructive force resulting from longitudinal chain network fractures was greater than that from transverse chain network fractures. Furthermore, within each region, the destructive force was inversely proportional to the number of threshing rows. In contrast, across different regions, this value was positively correlated with the number of threshing rows. The rate of change in force values within each region directly correlated with the impact angle. High-speed photography revealed that the transverse threshing process follows a spiral trajectory, whereas the longitudinal threshing trajectory aligns with the axial direction. The movement trajectories of maize kernels are all similar to parabolic movements. This study fills a gap in the study of airflow threshing for high water-content maize. Keywords: high velocity airflow, low velocity airflow, coupling, impact, maize threshing DOI: 10.25165/j.ijabe.20261901.961110 Citation: Li Y N, Li X P, Hou J R, Wang J Y, Peng B, Sun R Z. Experiment and method of maize ear threshing under airflow mixed impact. Int J Agric & Biol Eng, 2026; 19(1): 11–20.